The Correlation Between Exclusive Breastfeeding With Stunting Incident In Toddlers In The Bastem Utara Public Health Care - Alfrida Ronian Maliku; Grace Tedy Tulak; Abdullah Sappe Ampin Maja (USN Scientific Journal, 2020)
Stunting describes a lack of nutritional status that is chronic during times of growth and development from the beginning of life. This situation is presented with z-score height according to age (TB / U) less than -2 standard deviation (SD) based on growth standards. The purpose of this research was to analyze the Correlation of exclusive breastfeeding with the incidence of stunting in children under five in the Work Area of Bastem Utara primary health care. The research design used a cross sectional approach. The sample in this research amounted to 34 people with total sampling technique.The results showed that out of 34 respondents, 13 respondents (38.2%) with exclusive breasmilk included 10 toddlers (29.4%) with short stature and 3 toddlers (8.8%) with very stature short. And as many as 21 respondents (61.8%) did not provide exclusive breastmilk, including 3 toddlers (2.9%) with short stature and 20 toddlers (58.8%) with very short stature. Statistical test results using the chi square test showed that the p-value = 0,000 was smaller than the value of α = 0.05. The conclusion is there was a relationship between exclusive breastfeeding and the incidence of stunting in children under five in the Work Area of Bastem Utara primary health care.Based on the results of this research the authors propose suggestions, among others: expected to increase counseling in schools, Posyandu or cross-sectoral meetings in an effort to reduce the incidence of stunting. Birth attendant midwives are more motivating to support the success of exclusive breastfeeding, paying attention to the quality and quantity according to the needs of toddlers. Posyandu cadres to provide assistance to mothers from pregnancy to 6 months old toddlers for successful exclusive ASI.